Over-education, under-education and credentialism in the Australian labour market - Dockery, Alfred Michael; Miller, Paul (National Centre for Vocational Education Research (NCVER), 2012)
This report examines whether expansion in education has led to credentialism in the workforce. The authors employ the ‘ORU’ model to compare the required level of education for a job and the actual level which is held by an individual in that job. This model defines an individual as being over-educated (O) for their job, having the right level of education (R), or being under-educated (U). Credentialism is then measured against the benchmark ‘right’ level for older cohorts. Findings show that younger cohorts will suffer from credentialism to the extent that more of them are over-educated compared with the older cohort. The ‘bite’ of credentialism is then measured by the wage penalty associated with this over education. However, the penalty is a modest one and on the whole additional study results in skills which are rewarded by higher wages.